The Strange Career of a Black Utopia - Fabi, M. Giulia (Annali di Ca’ Foscari: Serie Occidentale, 2024)
This essay presents archival information about Charles H. Holmes and argues that his understudied novel, Ethiopia, The Land of Promise (1917), represents an important chapter in the history of Afrofuturism and American speculative fiction. The literary critical relevance of Ethiopia emerges forcefully from Holmes’s intertextual dialogue with other utopian and science fiction authors, such as Martin R. Delany, Sutton E. Griggs, Pauline E. Hopkins, Frances E.W. Harper, Edward Bellamy, and W.E.B. Du Bois. Holmes’s critique of Jim Crow segregation enables the articulation of a “distinctly revolutionary” project for African American futurity.